II.- Ecuaciones de 2º grado completas

     
1.164   1.165
     
x^{2}-7x+12=0   x^{2}-9x+18=0
     
     
1.166   1.167
x^{2}-9x+14=0   x^{2}-6x+8=0
     
     
1.168   1.169
     
x^{2}-6x+9=0   x^{2}+6x-27=0
     
     
1.170   1.171
     
x^{2}+6x=-9   x^{2}+9=10x
     
     
1.172   1.173
     
2x^{2}+10x-48=0   x^{2}-x=20
     
     
1.174   1.175
     
x^{2}-5x+6=0   \bg_black x^{2}+8x+15=8
     
     
1.176   1.177
     
x^{2}+10x+25=0   3x^{2}-39x+108=0
     
     
1.178   1.179
     
\bg_black 6x^{2}-37x+57=0   3x^{2}+2x=8
     
     
1.180   1.181
     
x^{2}=5x+6   x^{2}=5x+6
     
     
1.182   1.183
     
x^{2}-7x+3\frac{1}{4}=0   x^{2}-5\frac{3}{4}x=18
     
     
1.184   1.185
     
4x^{2}+12x=-9   5x^{2}+1=6x
     
     
1.186   1.187
     
12x^{2}-17x+6=0   10x^{2}+x=3
     
     
1.188   1.189
     
6x^{2}-12=x   x^{2}-512x+6000=0
     
     
1.190   1.191
     
2x^{2}+7x+6=0   4x^{2}+3x=8x
     
     
1.192   1.193
     
x^{2}+x+\frac{1}{4}=0   x(3x-2)=65
     
     
1.194   1.195
     
x+\frac{1}{x-3}=5   x^{2}-\frac{x}{2}=\frac{1}{3}-\frac{2x}{3}
     
     
1.196   1.197
     
\frac{x^{2}}{4}+2=\frac{3x}{2}   x+\frac{1}{x}=\frac{65}{8}
     
     
1.198   1.1979
     
x-2=\frac{4x-9}{x}   \frac{x}{2}+\frac{3}{x}=\frac{x+13}{3x}
     
     
1.200   1.201
     
\bg_black x+1=\frac{8x}{x-1}-4   \bg_black \frac{x+2}{x+1}+\frac{x+1}{x+2}=\frac{13}{6}
     
     
1.202   1.203
     
\bg_black \frac{16x^{3}-12}{2x^{2}-4}=6+8x   \frac{24}{x}+1=\frac{24}{x-2}
     
 
1.204
 
\frac{2x}{x-2}-\frac{x+2}{2}=1
 
 
1.205
 
x(x+1)+\frac{1}{4}\left ( x+\frac{3}{2} \right )=0
 
 
1.206
 
8x+11-\frac{7}{x}=\frac{21+63x}{7}
 
 
1.207
 
1+\frac{x+4}{3}=\frac{4x+7}{9}+\frac{7-x}{x-3}
 
 
1.208
 
\frac{x^{2}}{2}-\frac{3x}{5}=\frac{1}{5}-\frac{x}{6}
 
 
1.209
 
2x^{2}+\frac{6}{5}=x\left ( x+\frac{31}{5} \right )
 
 
1.210
 
\frac{5x^{2}}{8}-\frac{3x}{5}=\frac{x^{2}}{8}-\frac{x}{6}+\frac{1}{5}
 
 
1.211
 
\frac{5x^{2}}{6}-\frac{x}{2}+\frac{3}{4}=8+\frac{2x}{3}-x^{2}+\frac{273}{12}
 
 
1.212
 
\frac{2x-1}{x-1}=\frac{5(x-1)}{x+1}
 

Soluciones